Prenatal phthalate exposure and 8-isoprostane among Mexican-American children with high prevalence of obesity. (29th December 2016) - Tran, V.; Tindula, G.; Huen, K.; Bradman, A.; Harley, K.; Kogut, K.; Calafat, A. M.; Nguyen, B.; Parra, K.; Ye, X.; Eskenazi, B.; Holland, N.
Abstract : Oxidative stress has been linked to many obesity-related conditions among children including cardiovascular disease, diabetes mellitus and hypertension. Exposure to environmental chemicals such as phthalates, ubiquitously found in humans, may also generate reactive oxygen species and subsequent oxidative stress. We examined longitudinal changes of 8-isoprostane urinary concentrations, a validated biomarker of oxidative stress, and associations with maternal prenatal urinary concentrations of phthalate metabolites for 258 children at 5, 9 and 14 years of age participating in a birth cohort residing in an agricultural area in California. Phthalates are endocrine disruptors, and in utero exposure has been also linked to altered lipid metabolism, as well as adverse birth and neurodevelopmental outcomes. We found that median creatinine-corrected 8-isoprostane concentrations remained constant across all age groups and did not differ by sex. Total cholesterol, systolic and diastolic blood pressure were positively associated with 8-isoprostane in 14-year-old children. No associations were observed between 8-isoprostane and body mass index (BMI), BMI Z -score or waist circumference at any age. Concentrations of three metabolites of high molecular weight phthalates measured at 13 weeks of gestation (monobenzyl, monocarboxyoctyl and monocarboxynonyl phthalates) were negatively associated with 8-isoprostane concentrations among 9-year olds. However, at 14 years of age, isoprostane concentrations were positively associated with two other metabolites (mono(2-ethylhexyl) and mono(2-ethyl-5-carboxypentyl) phthalates) measured in early pregnancy. Longitudinal data on 8-isoprostane in this pediatric population with a high prevalence of obesity provides new insight on certain potential cardiometabolic risks of prenatal exposure to phthalates.